PTH-053 Colonoscopy: the doctors' gold standard, but is it the patients'? a study of choice of colonic investigation made by fully informed patients. (17th June 2017) - Ojidu, H; Lewandowski, J; Palmer, H; Hampton, J; Blakeborough, T; Epstein, O; McAlindon, M
Abstract : Introduction: Informed consent requires information about the nature, the risks, the benefits of the investigation proposed and the alternatives. [Brooks et al., Endoscopy 2005] Optical colonoscopy (OC) is widely accepted as the gold standard colonic investigative modality, but it is uncomfortable, incurs the risks of intubation and sedation and diagnostic yield is only 10% in symptomatic patients. [Gavin et al., Gut 2013] Alternatives include CT colonography (CTC) and colon capsule endoscopy (CCE) which are better tolerated and safer. The aim of this study was to determine the choices made by a cohort randomly selected from the population when provided with information about all three tests. Method: Members of the public were invited to take part in the study outside a local shopping centre. They were provided with written literature explaining the nature, and a summary table of the advantages and disadvantages, of each test and were free to ask questions of the research team. Patient tolerance and acceptability data was obtained from earlier studies of our patient population. [Ojidu et al., submitted to BSG 2017] The risk of serious complications (perforation, bleeding and radiation exposure), diagnostic yield and expected incidence of incidental pathology (polyps or extraluminal findings on CTC) were derived from published literature and patients were advised of the possible need for OC (if a non-invasive test identified a polyp or tumour) or further investigation if CTC identified extraluminal pathology, which they were told may or may not be important. They were asked to choose which test they would prefer for the investigation of two clinical scenarios: new symptoms and a positive faecal occult blood test in the bowel cancer screening programme (BCSP). Results: 100 subjects (median age (range) 42.5 years (19-92), 38% male) chose OC, CTC and CCE in 45%, 37% and 18% respectively to investigate new symptoms and 71%, 22% and 7% for the BCSP. Thus 55% of patients having symptoms investigated preferred an alternative to OC compared to 29% of those undergoing screening (p<0.001). There was a trend towards preference for a non-invasive test (CTC or CCE) in those aged 55 and over (73.3%) compared to younger patients (47.1%; p=0.17). Conclusion: Over half of a non-select cohort of the lay public prefer non-invasive colonic investigation of symptoms when fully informed about the modalities available, which should therefore be offered in clinical practice. Almost one third would prefer the same approach in the BCSP, which should be considered if compliance is to be optimised. Disclosure of Interest: None Declared